1996
DOI: 10.2307/1344522
|View full text |Cite
|
Sign up to set email alerts
|

When Is Stabilization Expansionary? Evidence from High Inflation

Abstract: Countries which stabilize from high inflation -here defined as an annual rate above 40% -usually have output expansions in the first and subsequent years of stabilization. These expansions occur in both exchange-rate-based and money-based stabilizations. The paper reaches these conclusions after examining a sample of all 28 episodes in the international data that meet a pre-defined criterion for stabilization from high inflation. The results do not change with alternative growth and stabilization definitions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 44 publications
9
90
1
2
Order By: Relevance
“…56 Fischer, Sahay, and Végh (1996, 1997) also find evidence for the transition economies in favor of expansionary stabilizations, with the expansions being more pronounced for the case of exchange rate-based stabilizations. Easterly (1996), however, has argued that expansionary stabilization is a more general feature of stabilization from high inflation countries, and occurs irrespective of whether the nominal anchor is the exchange rate or not. 57 We now proceed to revisit these important issues.…”
Section: B Real Variables In Disinflationmentioning
confidence: 99%
“…56 Fischer, Sahay, and Végh (1996, 1997) also find evidence for the transition economies in favor of expansionary stabilizations, with the expansions being more pronounced for the case of exchange rate-based stabilizations. Easterly (1996), however, has argued that expansionary stabilization is a more general feature of stabilization from high inflation countries, and occurs irrespective of whether the nominal anchor is the exchange rate or not. 57 We now proceed to revisit these important issues.…”
Section: B Real Variables In Disinflationmentioning
confidence: 99%
“…The former uses a mechanical rule to define a stabilization episode, whereas the latter uses well-known case studies in the economics literature to determine what can be considered an inflation stabilization plan. Easterly (1996) is a key paper in the mechanical tradition that holds stabilizations to be all episodes for which cross-country data show movement from two years or more of greater than 40 percent annual inflation to two years or more of less than 40 percent annual inflation. Hamann (1999) also advocates the use of mechanical rules defining more flexible criteria in order to determine what constitutes an inflation stabilization attempt.…”
Section: Data Sources and Samplementioning
confidence: 99%
“…Easterly (1996) in a study of a sample of stabilization programs has concluded that they are always expansionary. Kiguel and Liviatan (1992) and Ve´gh (1992) study the business cycles associated with ERBS in countries with chronic inflation, concluding that they differ greatly from those associated with MBS.…”
mentioning
confidence: 99%
“…In 1974 inflation moved into the high range where it stayed until 1984, averaging 49%. According to the terminology in Easterly (1996), there were two inflation crises during the high inflation period. The first, caused by the domestic response to the international oil crisis, occurred during 1974-75 and was followed by stabilisation in [1977][1978].…”
Section: A Summary Of the History Of Post-war Inflation In Icelandmentioning
confidence: 99%
“…Together with Iceland, Argentina is the only country in Easterly's (1996) sample which today has low inflation. 57 In fact, Argentina has done even better as it has gone from hyperinflation to virtual price stability in the course of just five years, whereas Iceland did not move into the low-inflation range until 1991, eight years after the first stage of disinflation.…”
Section: Argentinamentioning
confidence: 99%